2020
DOI: 10.14238/sp22.1.2020.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Luaran Terapi Gancyclovir dan atau Valgancyclovir pada Pasien Infeksi Cytomegalovirus di Instalasi Kesehatan Anak RSUP Dr Sardjito

Abstract: Latar belakang. Infeksi Cytomegalovirus (CMV) merupakan penyebab tersering infeksi kongenital anak di negara berkembang. Infeksi ini dapat menyebabkan tuli sensorineural (SNHL) dan gangguan perkembangan. Di RSUP dr Sardjito, pasien dengan infeksi CMV aktif bergejala akan menjalani terapi 6 minggu Ganciclovir atau 2 minggu terapi Ganciclovir dilanjutkan 4 minggu terapi Valganciclovir. Namun, luaran terapi tersebut belum diteliti lebih lanjut.Tujuan. Melihat luaran terapi ganciclovir dan atau valganciclovir pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…A study in 2008 showed that 16 mg/kg/dose of valganciclovir twice daily gave the same systemic exposure and plasma concentrations as intravenous ganciclovir in the disease. 5 Consistent with study in CMV-infected murine populations, it showed that treatment with ganciclovir would decrease viral load, ameliorate CMV-induced hearing loss, and attenuate outer hair loss. 1 Besides improvement in hearing function, valganciclovir has been effectively improved neurological too.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A study in 2008 showed that 16 mg/kg/dose of valganciclovir twice daily gave the same systemic exposure and plasma concentrations as intravenous ganciclovir in the disease. 5 Consistent with study in CMV-infected murine populations, it showed that treatment with ganciclovir would decrease viral load, ameliorate CMV-induced hearing loss, and attenuate outer hair loss. 1 Besides improvement in hearing function, valganciclovir has been effectively improved neurological too.…”
Section: Discussionsupporting
confidence: 61%
“…4 In the Pediatric Neurology Department, Dr. Sardjito General Hospital, Yogyakarta, there were 2-3 cases of CMV infection per month. 5 The transmission of CMV infection can occur vertically (from mother to fetus) in three ways: in utero through trans-placental exposure to viremia of CMV in maternal circulation, intrapartum during labor when the fetus is exposed to cervical and vaginal secretions containing CMV, and post-natally through ingestion of breast milk containing CMV or blood transfusion contaminated with CMV. 6,7 The percentage of viral transmission from mother to fetus is known to be about 30%, with 90% of fetuses remaining asymptomatic during the neonatal period.…”
mentioning
confidence: 99%